“Heróis” como nunca, “vilões” como sempre: racismo, humilhação e pandemia - o sofrimento ético-político dos entregadores de aplicativo em São Paulo - Raimundo, Mahasiãh (2024)
This paper deals with the theme of citizenship, race relations and app delivery workers/motoboys in the city of São Paulo, with the aim of accessing memories and analyzing the experience of what it was like to be an app delivery worker during the pandemic in terms of their affections and suffering. Under an ethnographic methodology inspired by action participant research, drifts were made through the streets of São Paulo, guided by the flow of walking and encounters in the city, to enter the daily lives of delivery workers. Narrative interviews and field diaries were used to mediate the meetings with the delivery workers. Secondary data from bibliographic documents and news portals was also used to complement the work's reflections. The theoretical framework for this research comes from socio-historical psychology, based on the reflections of Vygotsky and Lane on the understanding of subjectivity, Spinoza on the understanding of affections, and Sawaia on the proposal of the dialectic of social exclusion/inclusion and ethical-political suffering. In order to deepen the analysis of the affections and suffering experienced by motoboys during the pandemic, I relied on the theoretical category of Ethical-Political Suffering. This base reference is complemented by authors who discuss the precariousness and platformization of work and other Brazilian and foreign authors who discuss race relations and their social and subjective impasses. In the course of the research, it was possible to analyze that the dialectic of social exclusion/inclusion and the ethical-political suffering of app delivery workers pass through the racism sieve in a central way. During the pandemic, they were considered "heroes", but as the pandemic passed, they became "villains, as always", both for the app companies, whose motto was "precarious enough to keep them working and revenue increasing", and for the citizens of the city who have benefited and continue to benefit from their services, but who once again look at them as "monsters", provoking gestures of distrust and violence. Not resigned to it, the couriers use their own grammars to find ways of overcoming this suffering, reacting individually but also looking for common ground